Tinea corporis bullosa masquerading bullous pemphigoid - Neerja Puri (Journal of Pakistan Association of Dermatologists, 2022)
Introduction Tinea or dermatophytosis is one of the commonest infective dermatosis all over the world. Case report We presented a case of 60 years old male with multiple tense bullae mimicking bullous pemphigoid both clinically and histopathologically. Discussion The case we reported here had some typical dermatophytic features like erythematous annular lesions with central clearing and atypical features like bullous lesions with erosions. PAS stain revealed fungal hyphae and histopathology showed the presence of sub epidermal bulla